Simultaneous separation and quantitation of the major bovine whey proteins including proteose peptone and caseinomacropeptide by reversed-phase high-performance liquid chromatography on polystyrene–divinylbenzene - Elgar, David F.; Norris, Carmen S.; Ayers, John S.; Pritchard, Mark; Otter, Don E.; Palmano, Kate P. (Journal of Chromatography A, 2000)
A precise, sensitive and reliable RP-HPLC method was developed to enable not only unequivocal determination of α-lactalbumin and β-lactoglobulin in bovine whey samples, but also simultaneous measurement of proteose peptone, caseinomacropeptide, bovine serum albumin and immunoglobulin G. The optimised method on the Resource RPC column allowed separation of the proteins in 30 min and could be applied to the analysis of soluble proteins in a variety of commercial and laboratory whey products. Furthermore, some qualitative information on protein heterogeneity and quality could be derived from the RP-HPLC analyses with additional data available from on-line electrospray mass spectrometry. Within- and between-day repeatability over a wide range of concentrations was excellent (RSD≤5%) for all proteins except immunoglobulin G and bovine serum albumin where RSD was 7–10%. Analysis of grouped data from whey protein concentrate and whey protein isolate samples gave a limit of detection of ≤0.3% powder mass and a limit of quantitation of ≤1.0% powder mass for all proteins except immunoglobulin G. Limits of detection and quantitation were 0.6% and 2.0%, respectively, for this protein. Quantitative data obtained by the RP-HPLC method compared very favourably with data obtained by alternative methods of whey protein analysis.